Characterization and Impact of a Multidisciplinary Outpatient Pediatric Feeding and Swallowing Program - Benton, Kathryn; Delzell, Darcie; Nalepa, Nicole; Fishbein, Mark (Journal of developmental and physical disabilities, 2024)
Pediatric feeding disorders are common and are often associated with chronic medical conditions and developmental disorders. A multidisciplinary treatment approach may be offered through outpatient or intensive programs. Benefit has been demonstrated with intensive programs, but there is little data regarding outpatient approaches. We described outcomes from a well-established outpatient feeding assessment program related to the referral base and program outcomes. Study packets collecting demographics and self-reported feeding skills were distributed to the referral population and redistributed three months later. Standardized surveys implemented included Montreal Children’s Hospital Feeding Scale (MCH-FS) and parenting stress index (PSI-SF). One hundred and ninety-eight subjects completed the initial packet. MCH-FS was elevated in all subjects indicating a broad range of feeding concerns. PSI elevation was present in a broad range of comorbidities compared to group without comorbidities. At 3 months (n = 55), MCH-FS and feeding skills improved without change in PSI-SF. The quality of therapy overall was deemed excellent to above average by most subjects. A multidisciplinary outpatient program has a role in managing infants and children with feeding disorders regardless of comorbidity. Severely affected individuals may benefit from more intensive programs and/or may require long-term care to effect significant change.